A replication of four quasi-experiments and three facts from "The effect of file sharing on record sales: an empirical analysis" (Journal of Political Economy, 2007) - Stan J. Liebowitz (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
The influential piracy paper by Professors Oberholzer-Gee and Strumpf, although mainly based on proprietary data, contained an 'important complement' to the main results, consisting of four 'quasi-experiments' using publicly available data. This replication examines all of these quasi-experiments by using identical data and statistical methods where possible, as well as sometimes extending or augmenting the data or methods. This study concludes that the quasi-experiments performed by OS each contain important errors, oversights or inconsistencies that most often, but not completely, overturn the results claimed in the original OS article.
Keywords: Z1; O3; L8; 330; piracy; file sharing; sound recordings; music; iTunes; Napster